Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan di Golden Tulip Jineng Resort Bali Pada Masa Pandemi Covid-19 - Elisabeth Diora Jasmine; Ida Ayu Kalpikawati; Made Artajaya; Ni Wayan Chintia Pinaria (Journal of Hospitality Accommodation Management (JHAM), 2023)
This study aims to analyze the influence of the work environment and work motivation on employee performance at Golden Tulip Jineng Resort Bali during the Covid-19 Pandemic. The data collection technique used a questionnaire that was distributed to 40 hotel employees in the housekeeping department. The data from the questionnaire spread were analyzed using multiple linear regression. The results of the analysis show that (1) the work environment has a positive and significant effect on employee performance with a significance value of 0.002 < 0.1 (2) Work motivation has a positive and significant effect on employee performance with a signification value of 0.000 < 0.1. (3) There is a positive and significant influence together between the variables of work environment and work motivation on employee performance with a significance value of 0.000 <0.01 and a coefficient of determination of 63.7%. In this study, from the aspect of the work environment, it is expected to be one of the management's focuses to improve the employee's work environment, so that employees can work more productively and provide better results.